COVID-19 and other food shocks facing PNG - Schmidt, Emily; Diao, Xinshen; Dorosh, Paul A.; Fang, Peixun (Development Centre, 2021)
COVID-19 has impacted urban and rural households throughout Papua New Guinea (PNG). Looking ahead, policymakers and development practitioners must continue to mitigate COVID-19 impacts on PNG households, as well as monitor other potential agricultural production shocks (such as El Niño, African Swine Fever, etc.) that could substantially decrease household income and food consumption.